Exploring Living Space Quality through Socio-Economic Lens - Dr. Alka, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
A socioeconomic variable is a characteristic that can be measured and quantified to determine an individual's or group's social and economic status. Socioeconomic variables play a crucial role in determining the quality of living space available to individuals and communities. Variables such as income, literacy, poverty, population density, urban population, road density, and presence of SC/ST households are taken to find out the linkages with the Quality of Living Space. Karl Pearson’s correlation have been used to show the linkages. Result shows that there is a significant relationship between socio-economic variables and indicators pertaining to living space. Some indicators shows a positive relationship while others shows a negative relationship indicating a hope for the future.